Socioeconomic Status - Mortality Link; Do Race and Place Matter? - Shervin eAssari; Maryam eMoghani Lankarani (Frontiers Media S.A., 2016)
Abstract:Background: Despite the well-established literature on the protective effects of socioeconomic status (SES) against mortality, these effects may vary based on contextual factors such as race and place. Using 25-year follow up data of a nationally representative sample of adults in the U.S., this study had two aims: 1) to explore separate, additive, and multiplicative effects of race and place (urbanity) on mortality, and 2) to test the effects of education and income against all-cause mortality based on race and place.Methods: The Americans' Changing Lives (ACL) Study followed Whites and Blacks 25 years and older adults from 1986 until 2011. The focal predictors were baseline SES (education and income) collected in 1986. The main outcome was time to death due to all causes from 1986 until 2011. Age, gender, and behaviors (smoking and exercise) and health (chronic medical conditions, self-rated health and depressive symptoms) were potential confounders. A series of survey Cox proportional hazard models were used to test protective effects of education and income on mortality based on race and urbanity. Results: While race and place had separate effects on mortality, the additive and multiplicative effects of race and place were not significant. Higher education and income were protective against all-cause mortality in the pooled sample. While the protective effects of education was explained by baseline health, the effect of income remained significant beyond health. Race and urbanity significantly interacted with baseline education but not income on all-cause mortality, suggesting that protective effects of education but not income depend on race and place. Conclusion: The survival gain associated with education in the United States depends on race and place. These findings suggest that populations differently benefit from SES resources, particularly education. Differential effect of education on employment and health care may explain differential protective effect of education based on race and place. Findings support the diminishing returns hypothesis for Blacks.